Understanding zoonotic diseases - Romich, Janet Amundson (Thomson / Delmar Learning, 2008)
This book introduces the reader to microbes including bacteria, fungi, parasites, viruses, and prions, and describes specific diseases that can be transmitted from animals to humans. Extensive use of images, photographs, tables, and clinically relevant comments helps the reader understand the role of animals in causing diseases in humans